Macroeconomic and Financial Effects of Oil Price Shocks: Evidence for the Euro Area - Claudio Morana (Fondazione Eni Enrico Mattei (FEEM), 2016)
The paper investigates the macroeconomic and financial effects of oil prices shocks in the euro area since its creation in 1999, with a special focus on the recent slump. The analysis is carried out episode by episode, within a time-varying parameter framework, consistent with the view that "not all the oil price shocks are alike", yet without imposing any a priori identification assumption. We find evidence of recessionary effects triggered not only by oil price hikes, but also by oil price slumps in some cases, likewise for the most recent episode, which is also rising deflation risk and financial distress. In addition through uncertainty effects, the current slump might then be depressing aggregate demand by increasing the real interest rate, as ECB monetary policy is already conducted at the zero lower bound. The increase in real money balances following the slump points to the accommodation of the shock by the ECB, concurrent with the implementation of the Quantitative Easing policy (Q.E.). Yet, in so far as Q.E failed to generate inflationary expectations within the current and expected environment of soft oil prices, the case for a more expansionary use of fiscal policy than in the past would become compelling, in order to counteract the deflationary and recessionary threats to the euro area.
Keywords: E30; E50; C32; 330; Oil Price Shocks; Oil Price-macroeconomy Relationship; Risk Factors; Semiparametric Dynamic Conditional Correlation Model; Time-varying Parameter Models